Friday

April 18, 2014

April 18, 2014

Posted by **jhon** on Thursday, February 14, 2013 at 9:49am.

prove

- math -
**Steve**, Thursday, February 14, 2013 at 10:46amcosx/sinx + 2sinxcosx/cos2x

= (cosxcos2x + 2sin^2(x) cosx)/(sinxcos2x)

= cotxsec2x (cos2x + 2sin^2(x))

= cotx sec2x (1-2sin^2(x) + 2sin^2(x))

= cotx sec2x

**Related Questions**

Math - Prove 1+sec2x / tan2x = cotx

trig - (cotxsec2x - cotx)/ (sinxtanx + cosx) = sinx prove. i keep getting (if i ...

math - sin2x-cotx = -cotxcos2x Using the various trigonometric identities(i.e. ...

Trig - Prove the following functions: (sinx+sin2x)/(1+cosx+cos2x)=tan x (cos3x/...

trigonometry - Prove cotx-1/cotx+1=1-sin2x/cos2x

Math - 1)A piano tuner uses a tuning fork. If middle C has a frequency of 264 ...

Math - prove:(cscx-cotx)^4 x (cscx+cotx)^4 = 1

Math please help quick - Which of the following are identities? Check all that ...

maths - prove that if cotx(1+sinx)=4m and cotx(1-sinx)=4n, then (m^2-n^2)^2=mn

matj - prove that (cotx+tanx)(cotx-tanx) = 1/(sin^2 x) - 1/(cos^x)